2018
DOI: 10.1182/blood-2018-02-832535
|View full text |Cite
|
Sign up to set email alerts
|

SOX11 augments BCR signaling to drive MCL-like tumor development

Abstract: Mantle cell lymphoma (MCL) is characterized by increased B-cell receptor (BCR) signaling, and BTK inhibition is an effective therapeutic intervention in MCL patients. The mechanisms leading to increased BCR signaling in MCL are poorly understood, as mutations in upstream regulators of BCR signaling such as CD79A, commonly observed in other lymphomas, are rare in MCL. The transcription factor SOX11 is overexpressed in the majority (78% to 93%) of MCL patients and is considered an MCL-specific oncogene. So far, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 38 publications
0
34
0
1
Order By: Relevance
“…10,11,16 Oncogenic transformation associated with increased BCR signaling has been reported in murine B-cells overexpressing Sox11. 9 While the pro-B cell line in the present study lack the BCR, Sox11 was nevertheless able to significantly alter the global gene …”
Section: Ccl3mentioning
confidence: 67%
See 1 more Smart Citation
“…10,11,16 Oncogenic transformation associated with increased BCR signaling has been reported in murine B-cells overexpressing Sox11. 9 While the pro-B cell line in the present study lack the BCR, Sox11 was nevertheless able to significantly alter the global gene …”
Section: Ccl3mentioning
confidence: 67%
“…7,8 SOX11 overexpression has also been associated with increased B-cell receptor signaling and promotion of oncogenic transformation of B-cells in a murine model. 9 However, other studies report reduced cell proliferation upon SOX11 expression in MCL cells. 10,11 The non-malignant, IL-3 dependent pro-B cell line Ba/F3, which does not express immunoglobulins, 12 has previously been used for evaluating the transformation capability of potential oncogenes.…”
mentioning
confidence: 96%
“…Previous studies have shown the expression of vascular endothelial growth factor (VEGF) mRNA and protein in a limited number of MCL, but its relation to SOX11 expression was not investigated . Interestingly, SOX11 expression seems to induce higher activation of BCR signalling in MCL . One of the downstream effects of BCR signalling in these tumours was an increased expression of VEGF .…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of SOX11‐induced angiogenesis and PDGFA in the progression of the tumours was highlighted by the inhibition of tumour growth in animal models treated with the inhibitor of the PDGFA pathway imatinib . The biological differences between SOX11‐positive and ‐negative MCL include a large number of pathways and genetic alterations that may also influence angiogenesis and other relevant mechanisms . The more aggressive behaviour of the tumours may result from the integrative contribution of these mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation